In-Situ process monitoring during laser transmission welding of PA6-GF30 - Schmailzl, Anton; Quandt, Benjamin; Schmidt, Michael; Hierl, Stefan (Procedia CIRP, 2018)
Quasi-simultaneous laser transmission welding is preferably used for packaging sensors and electronics. In order to protect the components from moisture, a hermetic encapsulation is needed. However, local weld seam interruptions cannot be identified with the commonly used set-path monitoring. By using a pyrometer, coaxially integrated into a 3D-scanner, gaps between the joining partners can be allocated on basis of the measured temperature. However, the scattering of the heat radiation, especially caused by the fiber reinforcement of the plastics, leads to a reduction of the accessible heat radiation, which makes the identification of gaps considerably more difficult. The herein used experimental setup is characterized by a small detection spot and only by a slight weakening of the heat radiation inside the scanner. Hence, for welding PA6-GF30, the detection of small sized gaps is possible, even if a glass fiber content of 30 percent (wt.) and a weld seam width with approximately 1 mm are given.
Created from Fastlane, Scopus look-up
Keywords: "; "in-situ monitoring; Fiber reinforced plastics; Plastics welding; Pyrometer; Temperature measurement